2000
DOI: 10.1097/00005344-200004000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins and Blood Pressure Control in Treated Hypertensive Patients with Hypercholesterolemia

Abstract: High serum cholesterol has been frequently reported in patients with arterial hypertension in whom it might influence the blood pressure control. The aim of this study was to compare the extent of blood pressure changes in 41 patients with hypertension and hypercholesterolemia, taking antihypertensive drugs and treated for 3 months with statins (HC-S; pravastatin or simvastatin) and compared with matched controls with high (HC-D; 44) or normal serum cholesterol (NC-D; 45) undergoing antihypertensive treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 31 publications
7
89
2
2
Order By: Relevance
“…Alternatively, antihypertensive therapy may affect the BP-lowering effect of statins. In previous studies, 7,8 70-100% of patients received angiotensin-converting enzyme inhibitors, whereas only 32-36% of the patients in the present study had taken angiotensin-converting enzyme inhibitors, and possible interaction with angiotensin-converting enzyme inhibitors may play an important role in the BP-lowering effect of statins.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Alternatively, antihypertensive therapy may affect the BP-lowering effect of statins. In previous studies, 7,8 70-100% of patients received angiotensin-converting enzyme inhibitors, whereas only 32-36% of the patients in the present study had taken angiotensin-converting enzyme inhibitors, and possible interaction with angiotensin-converting enzyme inhibitors may play an important role in the BP-lowering effect of statins.…”
Section: Discussioncontrasting
confidence: 53%
“…7,8 However, the results of the present study clearly demonstrated that long-term use of pravastatin, simvastatin, fluvastatin, and nonstatin antihyperlipidaemic drug had no additional effect on BP but significantly decreased the serum TC levels in hypertensive patients with high serum TC levels and insufficiently controlled BP despite antihypertensive therapy. This discrepancy may be attributable to the longer treatment period in the present study: the patients in previous studies received statins for only 3 or 4 months, whereas our patients received statins for 12 months.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Previous clinical trials reported a blood pressure lowering effect of statins in hyperlipidemic hypertensive patients who were not taking any antihypertensive drugs [39] and who had already received antihypertensive therapy [40][41][42]. The mechanisms of the reduction of blood pressure by statins in these patients included the activation of endothelial nitric oxide synthase [43], the downregulation of angiotensin II type 1 receptors [44], and a reduction in the vascular production of ROS [45].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that cardiologists have a deep conviction in the efficacy of statins compared with the other lipid-lowering agents. In addition to their lipid-lowering effect, statins have been reported to improve blood pressure control in hypertensive patients who have concomitant hyperlipidemia; moreover, statins are well known to prevent cardiovascular diseases (19)(20)(21)(22)(23)(24). All these beneficial effects have led physicians to consider statins as a useful intervention for atherosclerotic diseases (25).…”
Section: Drug Treatment Of Hyperlipidemiamentioning
confidence: 99%